Balance of monodualistic principles in different efforts at the level of investigation on child abuse of narcotics crime - Bernat Panjaitan; Risdalina Risdalina; Kusno Kusno (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Based on the setting for determining criminal policies that are in accordance with the values of people's lives, the setting for determining criminal policies is contained in the Criminal Code as general provisions and in the special criminal provisions of Law No. 35 of 2009 as a special crime that regulates narcotics. Based on this, the problem that will be discussed is how the monodualistic principle in eradicating criminal acts of narcotics abuse committed by children is contrary to the law related to Law No. 35 of 2009 and Law No. 11 of 2012. This research is normative juridical research, namely research conducted by examining library materials or secondary data. In terms of implementing the diversion, there are several things that make it impossible. There are several factors that cause the diversion of children who abuse narcotics to not be achieved,namely internal and external factors. @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;